Microbial contamination on beef trade in wet markets of Lambaro, Sigli, and Meureudu, Aceh Province, Indonesia - . Razali; . Nurliana; Teuku Reza Ferasyi (Syiah Kuala University, 2013)
Food animal origin such as beef is one of the basic needs for our society. Some cases of disease caused by microbial contaminated livestock product have been reported in Indonesia. It means that food safety has to obtain serious attention. Someefforts byobservationandexamination ofthe number ofmicrobial contaminationon beefin three wet marketswere considered important to assessthe extent ofmicrobial contamination compared with thethresholdset by theIndonesiangovernment throughthe NationalStandards. The results ofbeef sample examinationand assessmentby theVeterinary PublicHealth Laboratoryof the Faculty of Veterinary Medicine of Syiah Kuala University on thenumber ofmicrobial contamination of Total Plate Count (TPC) from the wet markets ofLambaro(Aceh BesarDistrict), the Sigli(PidieDistrict), and Meureudu(PidieJaya District) showed thatmicrobial contaminationis belowthe threshold setSNI-3932-2008. In general, the results showed that the qualityof food productsof animal origin,particularly beeffrom wet marketsinthreedistricts,have levels of contamination that arestill reasonable. Nevertheless,goodhygiene andsanitationsupervisionofpre-productionto distributionandcirculation of supervision should be maintained.